Understanding the origin of 35/37Cl and 16/18O isotope effects on 195Pt and 103Rh NMR nuclear shielding in selected Pt(IV) and Rh(III) complexes : a DFT study - Davis, John Christopher (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.